Intrinsic Fluorescence Excitation–Emission Matrix Spectral Features of Cottonseed Protein Fractions and the Effects of Denaturants. (13th June 2014) - He, Zhongqi; Uchimiya, Minori; Cao, Heping
Abstract: To better understand the functional and physicochemical properties of cottonseed protein, we investigated the intrinsic fluorescence excitation–emission matrix (EEM) spectral features of cottonseed protein isolate (CSPI) and sequentially extracted water (CSPw) and alkali (CSPa) protein fractions, and the effects of denaturants urea, guanidine hydrochloride, and sodium dodecyl sulfate. The EEM showed two contour peaks at the excitation wavelengths of 226 nm (Peak 1) and 277 nm (Peak 2). Addition of denaturants gradually shifted the emission maxima of both peaks from 335 nm to around 353 nm for CSPI and CSPa. The emission maximum (353 nm) of CSPw was unchanged by denaturation. These observations indicated that the tryptophan residues (fluorescence source) in the native CSPI and CSPa were protected within the micro hydrophobic environment, and gradually become water accessible with progressing denaturation. On the other hand, the tryptophan residues in native CSPw were already in contact with water. However, the fluorescence intensity of Peak 1 of all three protein samples decreased with increasing denaturant concentrations, suggesting similarity in some conformational changes in the three samples. Further exploration of the fluorescence mechanism of Peak 1 is needed to understand such similar conformational changes.